177 A case of cervical embryonal botryoidal rhabdomyosarcoma. (18th September 2019) - Godfrey, M; Yeoh, CC; Rahimi, S; Akaev, I; Khanapure, A; Gardner, F
Abstract : Objectives: Embryonal rhadbomyosarcoma (RMS) is a rare, highly malignant tumour, primarily seen in the pediatric and adolescent population. It is rare in patients above 40 years of age. RMS arises from immature cells destined to form striated skeletal muscle. Around 20% of RMS in childhood arise in the genitourinary tract. The infantile vagina is the most common site. The cervix is a rare site of the disease even in children and adolescents. These lesions are usually embryonal. The botryoid types are usually detected in a child under 8 years. Prognosis of RMS was poor until the introduction of neoadjuvant chemotherapy. Methods: Patient had a polypoid mass in cervix 3cm-by-3cm, with normal appearing surrounding ectocervix and vagina. The biopsy was consistent with embryonal RMS. MRI showed a complex polypoidal mass which appeared to be arising from cervix. CT Chest/abdomen and pelvis scan was clear of distal disease. Molecular genetic was sent for germline-DICER1 mutation. Supplementary video of this surgical resection is attached. Results: The Sarcoma Cancer Centre recommended following a risk-adapted strategy for patient: - for her: age (>11 yrs) is unfavourable but histology site is favourable. Size (5 cm) is on the cusp. She had IVA chemotherapy (ifosphamide/vincristine/dactinomycin). She had positive margins after loop excision, so also had a trachelectomy. Embryonal RMS of the cervix must be distinguished pathologically from adenosarcomas with heterologous elements, malignant mixed Müllerian tumours and low-grade stromal sarcomas. Conclusions: Cervical RMSs seems to have a better prognosis than similar tumours arising from other sites of the female genital tract.